2018
DOI: 10.15611/pn.2018.503.28
|View full text |Cite
|
Sign up to set email alerts
|

Is Accounting in Poland a Woman?

Abstract: Przedmiotem rozważań w artykule jest płeć (gender) w rachunkowości, a jego głównym celem jest zbadanie "obecności" kobiet i mężczyzn w polskiej rachunkowości. Dla realizacji tego celu przyjęto metodę studiów literaturowych, metody ilościowe oraz analizę opisową i porównawczą. W pierwszej kolejności, na podstawie analizy literatury, naświetlono, czym zajmują się gender studies w rachunkowości. Następnie, przy wykorzystaniu danych pochodzących z blisko 100 źródeł, przedstawiono "obecność" kobiet i mężczyzn w obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Table 5 displays the structure of the sample through the age and gender dimensions. Similarly to previous studies (Kabalski and Szwajcar, 2015;Masztalerz, 2018), our sample also reveals the feminization of the accounting profession in Poland. Table 6 shows the outcome of normality test for variables: none of the variables are normally distributed (Shapiro -Wilk W test).…”
Section: Data Descriptionsupporting
confidence: 76%
“…Table 5 displays the structure of the sample through the age and gender dimensions. Similarly to previous studies (Kabalski and Szwajcar, 2015;Masztalerz, 2018), our sample also reveals the feminization of the accounting profession in Poland. Table 6 shows the outcome of normality test for variables: none of the variables are normally distributed (Shapiro -Wilk W test).…”
Section: Data Descriptionsupporting
confidence: 76%
“…It includes 54 women and 9 men. The disproportion between female and male respondents is caused by a feminization of accounting-related studies and jobs in Poland, as revealed by many studies (Czarniawska, 2008;Kabalski, 2022;Masztalerz, 2018). The mean age of respondents is ca.…”
Section: Methodsmentioning
confidence: 99%
“…In this unique setting, accounting studies are highly feminized [30,31] and highly desired in Poland. It is not surprising that one particular field of study in Poland is usually chosen by one gender, as in Poland generally there is no gender parity at the tertiary educational level.…”
Section: Introductionmentioning
confidence: 99%